Theology remixed Christianity as story, game, language, culture - English, Adam C., 1974- (Downers Grove, Ill. : IVP Academic, 2010)
Christianity is like a story with scenery, characters and plots. It's like a language with vocabulary, grammar and conversation. It's like a game with rules and players, goals and equipment. It's like a culture with a distinct way of living, working, playing and loving. No one analogy is complete, but all offer new windows of appreciation for the faith. --from publisher description
To what shall I compare it? -- Christianity as story -- Christianity as story : creations and catastrophes -- Christianity as story : reconciliation -- Christianity as story : endings and beginnings -- Christianity as language : language training -- Christianity as language : learning a new tongue -- Christianity as language : making substitutions -- Christianity as game -- Christianity as game : players -- Christianity as game : equipment -- Christianity as game : reading rules -- Christianity as culture -- Christianity as culture : the worshiping colony -- Christianity as culture : cultivating the harvest -- On behalf of new things.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Philosophical theology; Christianity -- Philosophy; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books